Enhancing Productivity in Freshwater and Bracket Fisheries in Buru District, Maluku Province, Indonesia - Yuli Andriani; Rusky I. Pratama; Irfan Zidni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The fisheries sector, a vital economic force in Buru, Maluku Province, faces suboptimal conditions, notably in the unexplored potential of freshwater aquaculture due to limited human resources and skills. This study aims to comprehensively explore and develop aquaculture, providing a focused, integrated approach from upstream to downstream sectors. Success indicators and references are established to guide targeted achievements, benefiting the Local Government and Regional Development Planning Agency in Buru. Employing field observation and discussions, the findings reveal the conventional nature of current freshwater aquaculture practices, emphasizing the urgent need for bolstering technical, operational, and managerial aspects in the sector for optimal productivity